Learning from Developing Country Power Market Experiences : The Case of Colombia - Rudnick, Hugh; Velasquez, Constantin (World Bank, Washington, DC, 2019)
The Colombian power market was established in 1995, driven primarily by concerns about the reliability of supply in the largely hydro-based domestic power system. The power sector reform was expected to help avoid blackouts by attracting private investment and increasing the efficiency of existing capacity. However, two decades after its inception, the market has not been successful in providing reliable supply along competitive outcomes. This paper analyzes the experience of Colombia with power markets, including market design, implementation, and outcomes. A single-node, bid-based market was established overnight, with bilateral contracts among market participants (mostly short-to-medium term). The original regulated capacity payment was replaced in 2004 by a reliability market intended to ensure supply during tight hydrological conditions (mainly due to El Nino phenomena). However, the Colombian power sector is currently showing signs of structural weakness: the reliability market has shown dysfunctionalities, the government has intervened the market during critical situations, and concerns persist regarding market power exercise. The experience of Colombia is important for other developing countries, since it highlights the challenges of designing and implementing a power market that successfully provides reliability, competitive outcomes, and sustainability. Although key local hydrological conditions were considered in the design of Colombia's capacity market, the market had difficulties delivering intended outcomes due to design and institutional issues, particularly the lack of a comprehensive approach to gas supply and transport.